Teacher Collaboration in Managing Islamic Religious Education Classes in Inclusive SDIT Ibnu Taimiyah Bandung - Helmy Abdullah Helmy; Intan Wardatul Karimah; Nurti Budiyanti (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2026)
Abstract Inclusive education requires effective interprofessional collaboration to ensure equitable learning access for students with special needs, particularly within Islamic Religious Education (IRE) in inclusive school contexts. This qualitative case study examines collaboration between Islamic Religious Education teachers and Special Education Support Teachers (SEST) in managing inclusive IRE learning at an Integrated Islamic elementary school (SDIT) in Bandung, focusing on planning, implementation, and evaluation. Data were collected through semi-structured interviews and document analysis and analyzed using an interactive thematic approach. The findings indicate that structured co-teaching collaboration characterized by clear role delineation, shared planning, routine pre-instructional communication, responsive differentiation, dynamic role rotation, and dual-track evaluation supports effective inclusive IRE learning while maintaining curriculum standards. This collaborative approach enhances engagement, social adaptation, and confidence among students with special needs without marginalizing their participation in collective religious learning. However, institutional capacity constraints, selective admission policies, limited continuous professional development, and gradual technology integration remain significant challenges. The study concludes that context-sensitive collaboration models grounded in Islamic values such as empathy, cooperation (ta’awun), and justice are essential for strengthening inclusive IRE learning management and advancing equitable educational practices in Indonesian inclusive elementary schools. Keywords: Co-Teaching, Inclusive Education, Islamic Religious Education, Students with Special Needs, Teacher Collaboration